رأس المال الفكري والمؤسسات الصغيرة والمتوسطة بالجزائر - دريس, يحي; محرز, صالح (جامعة الوادي - University of Eloued, 2018)
لقد أصبح ينظر إلى رأس المال الفكري باعتباره ممثلا حقيقيا لقدرة المؤسسات على المنافسة وتحقيق النجاح، وهذا بعد تحول الاقتصاد إلى اقتصاد قائم على المعرفة، فرأس المال الفكري هو الأصل الجديد وهو أحدث عوامل الإنتاج الذي يعترف به كمورد أساسي لإنشاء الثروة بل والأكثر أهمية من عوامل الإنتاج التقليدية الأخرى كالعمل ورأس المال والمواد الأولية. ويلعب رأس المال الفكري دورا مهما في دعم الميزة التنافسية المستدامة، وتحقيق الكفاءة والفعالية التنظيمية ونجاح المؤسسات بمختلف أنواعها. وتهدف هذه الدراسة إلى التعرف على دور رأس المال الفكري في تحقيق الميزة التنافسية للمؤسسات الصغيرة والمتوسطة. Intellectual capital is being viewed as the real representative concerning the ability of any company to compete or to make success especially after the gradual economic change to the economy based on knowledge. So Intellectual capital becomes the new basis and the most modern production’s factor which regard it as the essential resource to the erection of fortune even more important than the traditional factor of production such as : work, capital and raw materials. Intellectual capital plays important role to support sustained competitive advantage and achieve organizational efficiency , effectiveness , and organizational success.This study aims to study the role of Intellectual capital in achieving the competitive advantage.
Intellectual capital and small and medium enterprises in Algeria
مقال
Keywords: رأس المال الفكري؛ المؤسسات الصغيرة والمتوسطة.; Intellectual capital; small and medium enterprises